PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI SPARKOL VIDEOSCRIBE PADA MATA PELAJARAN GEOGRAFI KELAS XI DI SMA NEGERI 5 KUPANG - Wadu, Mariana Rodjo; Samin, Mikael; Pamungkas, Bella Theo Tomi (Universitas Nusa Cendana, 2022)
This study aims to (1) determine the development of learning media based on the Sparkol Videoscribe application in the geography subject of class XI at SMA Negeri 5 Kupang, (2) determine the feasibility of the learning media developed, and (3) determine the responses of teachers and students to the use of media. learning. The type of research used is Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, and evaluation). The research subjects were 50 students in class XI, and 1 teacher for geography in class XI. Data collection techniques using questionnaires and interviews. The results of the study were in the form of learning media based on the Sparkol VideoScribe application. The developed media met the criteria for media quality with the results of the validation of media experts in the very appropriate category, 87% and 79% by material experts in the appropriate category. Meanwhile, the teacher's response to the learning media trial was 85%, the response of 10 students to the small scale trial was 83% and the response of 40 students to the large scale trial was 84%, all of which were categorized as very feasible. So, it can be concluded that the learning media developed based on the Sparkol VideoScribe application in class XI geography subjects at SMA Negeri 5 Kupang is suitable for use in the learning process and it is recommended that teachers use Sparkol VideoScribe in designing learning media as an alternative to improve the quality of learning.